Structural aspects of the Co/ZrO2 catalytic system: Effect of the chemical synthesis - Lick, Ileana Daniela (2005)
In this work, the application of the Co/ZrO2 catalytic system was studied as catalyst for the reaction of selective reduction of nitrogen oxides with propane in oxygen presence. Particularly, the influence of the preparation method on the catalytic activity of these materials was studied. It was possible to observe that the activity depends, markedly, on the physicochemical properties of the material and these ones on the preparation method. The catalyst that shows higher activity is the one that presents a crystalline structure, preferably, monoclinic, where the cobalt is present as Co2+ species occupying tetrahedral sites and these cobalt species do not present reduction up to 1000 °C.